Comparison between the single deepest pocket and amniotic fluid index in predicting fetal distress in small‐for‐gestational age fetuses - Tsunetake Miyamura; Hideaki Masuzaki; Masashi Miyamoto; Tadayuki Ishimaru (Acta Obstetricia et Gynecologica Scandinavica, 1997)
Background. The relationship between reduced amniotic fluid volume and increased risk of fetal distress in small‐for‐gestational age fetuses is not yet clear. Furthermore, the criteria used for the diagnosis of ‘oligohydramnios’ are different between the single deepest pocket method and amniotic fluid index. We investigated the relationship between the single deepest pocket and amniotic fluid index and their ability in predicting fetal distress in small‐for‐gestational age fetuses. Method. We examined 69 pregnant women with singleton pregnancy, intact membranes, birth weight below the 50% percentile − 1.5 s.d., in whom delivery occurred within seven days of the last estimation of amniotic fluid volume. Amniotic fluid volume was measured in each woman simultaneously by single deepest pocket and amniotic fluid index. Fetal distress was determined by intrapartum monitoring of fetal heart rate. Results. Estimates of amniotic fluid volume measured by the two methods showed a significant correlation at 24 to 41 weeks of gestation. A cut‐off value for single deepest pocket of 3.0 cm was associated with the highest accuracy in predicting fetal distress in small‐for‐gestational age fetuses. The rate of cesarean section among patients with single deepest pocket <3.0 cm was higher than that in amniotic fluid index < 8.0 cm. Conclusion. Our results demonstrated that a single deepest pocket measurement of < 3 cm is the most useful criterion for ‘oligohydramnios’ in the prediction of fetal distress.